STUDY ON APPLICATION OF THIN CELL LAYER CULTURE FOR IN VITRO PROPAGATION OF CHRYSANTHEMUM INDICUM - Van Viet, Nguyen (Journal of Forestry Science and Technology, 2024)
Chrysanthemum indicum L. is a common flower which can bring highly economic, C. indicum is on of the most important cut flower and pot plant. Thin cell layer (TCL) culture is a potential method for in vitro propagation of C. indicum. However, this method is still limited in Vietnam. After sterilization with HgCl2 0.1% solution for 6 minutes and being cultured on Murashige T. and Skoog F. (1962) (MS) medium supplemented with 6-benzyl amino purine (BAP) 0.5 mg/l, α-naphthaleneacetic acid (NAA) 0.2 mg/l, sucrose 30 g/l, agar 7 g/l, the cultured samples were recorded with survival percentage of 81%, shoots were generated after 4 weeks. Callus induction and shoot regeneration on MS medium supplemented with BAP 0.5 mg/l, kinetin 0.2 mg/l, NAA 0.2 mg/l were obtained with 82.2% and 80%, respectively.